Agrobiodiversidad y soberanía alimentaria en la parroquia Peñaherrera, cantón Cotacachi - Sánchez Céspedes, Ima Sumac (2014)
The objective of this research was to evaluate if the knowledge and agrobiodiversity practices of Peñaherrera’s people, lead to biodiversity conservation and food sovereignty. To achieve it, there were selected three farms at Peñaherrera’s parish. The farms were located at different altitude and had different characteristics. There was carried out an inventory of species and varieties with known uses by farmers and their families for each agroecosystem. By this way 97 species were identified; species richness per farm was 46, 30 and 65 respectively; while the Margalef diversity index showed that farm 3 has value exceeding 5, considered high, while diversity of farm 2 is medium. The Agrobiodiversity Index (IDA) was applied for first time in Ecuador. For this purpose, farm biodiversity was classified in separate in four species groups (human food; animal feed, feed the soil and complementary biodiversity) and there was assigned a value taking into account the importance of each species in the ecosystem. Farm 3 achieved the highest IDA value, but still does not reach the appropriate value reported in literature; the farmers should consider calculated sub-indices in order to include in their farm plants to rise actual indices; only in this way agroecosystem sustainability could be achieved by becoming an integrated, functional and balanced system towards community’s food sovereignty.